Case Report: A case series on histiocytic sarcoma – various clinical features and patient outcomes - Nam, Hohyung; Min, Gi-June; Kim, Tong Yoon; Jeon, Youngwoo; Cho, Seok-Goo (Frontiers in Oncology, 2025)
IntroductionHistiocytic sarcoma (HS) is a rare and aggressive hematologic malignancy with a poor prognosis. HS can present with either isolated organ involvement or multi-systemic disease. This case series reports on nine patients with diverse clinical presentations and outcomes.MethodsDiagnoses of HS were confirmed using immunohistochemistry, with markers such as CD68 and lysozyme. Treatment primarily involved anthracycline-based chemotherapy with autologous hematopoietic stem cell transplantation (auto-HSCT) consolidation, and with salvage therapies for resistant or relapsed cases including allogeneic HSCT (allo-HSCT).ResultsDespite intensive treatment, long-term remission was rare. Among the nine patients, three achieved complete remission but relapsed, three had stable disease, two experienced progressive disease, and one is under treatment. No patient maintained complete remission for at least three years, indicating the chemo-resistant nature of HS. Moreover, of three cases in our cohort that achieved complete remission, two declined auto-HSCT owing to the intensity of first-line chemotherapy, and one relapsed shortly after achieving remission. To overcome chemo-resistance, four patients underwent allo-HSCT, and two of them achieved long-term remission.ConclusionThese findings highlight the importance of early diagnosis and suggest potential benefits of either autologous or allogeneic transplantation, while emphasizing the need for further research on treatment protocols.